Caribbean Court of Justice : the history and analysis of the debate - Rawlins, Hugh (CARICOM Secretariat GeorgetownGY, 2000)
Provides a chronical of the history of the debate on the establishment of a court of final appellate jurisdiction, or apex court in the Caribbean.